A 'don't eat me' immune signal protects neuronal connections. (1st November 2018) - Rivest, Serge
During development, some synaptic connections between neurons are removed by immune cells called microglia, and others are retained. The discovery of a 'don't eat me' signal that prevents excess pruning sheds light on this process. During development, some synaptic connections between neurons are removed by immune cells called microglia, and others are retained. The discovery of a 'don't eat me' signal that prevents excess pruning sheds light on this process.